Deconstructing bubble: determinants and prices of housing in Colombia (2015)
This paper seeks to analyze the behavior of housing prices in Colombia, to associate items to the presence of a housing bubble or favoring its creation, making a contextualization and conceptualization, that will address the Colombian market housing, using elements both theoretical and empirical, the latter, based on historical experience and on observation of facts that allow confronting it with what is currently happening in our country.